Ep.1 - Violences invisibles - Les violences psychologiques et économiques - VIOLENCE QUE FAIRE (2021)
Les violences psychologiques et économiques au sein du couple, qu'est-ce que c'est ? En quoi sont-elles différentes d’un conflit ordinaire ? Comment s’installent-elles ? Quelles en sont les conséquences et comment s’en sortir ? Mêlant l'analyse du Docteur Emmanuel Escard, Médecin adjoint responsable de l'Unité Interdisciplinaire de Médecine et de Prévention de la Violence (UIMPV) et de nombreux extraits de témoignages d'anciennes victimes, Poussière apporte un éclairage sur ces questions. Vous ou l'un-e de vos proches êtes concerné-e-s par les violences au sein du couple ? Vous n'êtes pas sûr-e ? Posez votre question sur www.violencequefaire.ch et un-e professionnel-le vous répondra dans un délai de trois jours ouvrables. Un podcast de VIOLENCE QUE FAIRE Réalisation: Julia Guglielmetti Graphisme : Julia Guglielmetti Musique : Pylone (Valentin Perroud) - Bloom
Keywords: approches et analyses; cours; discipline; médecine; pol5480; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences; thématiques; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis